2003
DOI: 10.1080/00288233.2003.9513547
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring long‐term changes in reserve potassium in some New Zealand soils using a modified sodium tetraphenyl‐boron method

Abstract: Changes in reserve-K status were measured on a number of historical and current pasture trials using a modified sodium tetraphenylboron incubation method (TBK incubation).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Instead, the large variability indicated that a comprehensive sampling regime would be required to estimate Step K for each field. Carey and Metherell (2003) reached a similar conclusion in a study of long-term fertilizer trials conducted on New Zealand soils with sedimentary parent materials.…”
Section: The Second Surveysupporting
confidence: 59%
“…Instead, the large variability indicated that a comprehensive sampling regime would be required to estimate Step K for each field. Carey and Metherell (2003) reached a similar conclusion in a study of long-term fertilizer trials conducted on New Zealand soils with sedimentary parent materials.…”
Section: The Second Surveysupporting
confidence: 59%
“…Cox et al (1999) showed in a pot trial study that shorter extraction times using NaTPB may be preferable to longer-term extractions as a measure of plant available-K. However, extrapolations to the field from pot trials can prove problematic for a variety of reasons (Carey and Metherell 2003a).…”
Section: Soil Test Methodologymentioning
confidence: 99%
“…The unexplained portion of the K balance is assumed to be mainly due to changes in soil K below the standard sampling depth (0-7.5 cm) (Carey and Metherell 2003a). The methodology for extraction of reserve K using NaTPB differs from cation exchange-based soil test methodologies such as QTK in that the removal of K from soil mineral interlayers is kineticallycontrolled (Chute and Quirk 1967;Cox and Joern 1997).…”
Section: Soil Test Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…While K exch can reach steady state at a low level when K balance is negative for a long time (Blake et al 1999, Madaras andLipavský 2009), a decrease of K reserves is clearly measurable in K non-exch pool (Carey and Metherell 2003, Andrist-Rangel et al 2007. K exch monitoring therefore might not give a true impression about the development of soil K reserves (Madaras 2014).…”
mentioning
confidence: 99%